Role of dihydropyridine calcium channel blockers in coronary bypass surgery using the radial artery graft - V. V. Zatolokin; Yu. Yu. Vechersky; D. V. Manvelyan; B. N. Kozlov (Российский кардиологический журнал)
Aim. To assess the effect of a pharmacological protocol for the prevention of radial artery spasm, which is based on the systemic and local use of dihydropyridine calcium channel blockers, on the long-term outcomes of autoarterial coronary artery bypass grafting.Material and methods. According to the protocol, oral nifedipine at a dose of 5 mg/day is prescribed 3 days before surgery. Then, after the radial artery is isolated, the vessel is preserved in a solution of nifedipine (adalat) until it is used. After releasing the clamp from the aorta, a nifedipine (adalat) is infused intravenously at a dose of 0,63 mg/h. In the postoperative period, the infusion of nifedipine continues for 6 hours. In the future, patients are recommended to take dihydropyridine calcium channel blockers at a dose of 5 mg/day after discharge from the hospital.Results. The use of the pharmacological protocol (n=225) is associated with a lower number of major cardiovascular events (mortality, myocardial infarction, stroke) compared with the control group (n=230) (9,3% and 15,7%, p=0,031) during the 5-year follow-up. This result was achieved mainly by reducing the incidence of myocardial infarction (6,2% and 12,6%, p=0,018). Also, the use of the pharmacological protocol led to a decrease in repeated revascularizations (4,4% and 16,1%, p=0,0001) compared with the control group.Conclusion. The use of a pharmacological protocol for the prevention of radial artery spasm based on the systemic use of dihydropyridine calcium channel blockers improves the long-term outcomes of autoarterial coronary artery bypass grafting.